Institutional Management Failures and Maladministration in One-Stop Integrated Public Services (PTSP): A Qualitative Case Study at Jambi City's Public Service Mall (MPP) - Noviardi Ferzi; Nuraida Fitri Habi; Ardian Kurniawan (Politeknik Siber Cerdika Internasional, 2026)
Background: This research investigates the forms of maladministration that occur in the management of One-Stop Integrated Service Center (PTSP) City Jambi. Objective: To determine the key managerial factors contributing to maladministration and their impact on the quality of services provided by public enterprises. Methods: A qualitative approach with a case study design was applied, with data collected through in-depth interviews involving PTSP officials, clients, and members of the Indonesian Auditors’ Board (BPK), accompanied by an analysis of relevant policies and institutional documents. Informants were purposively sampled to ensure rich data and validation until theoretical saturation was achieved. Results: The findings indicate that maladministration remains a serious issue in the PTSP of Jambi City, manifesting in various forms, such as the absence of an integrated complaint system, subjective application of procedural transparency, and persistent delays in service delivery. These problems are corroborated by the audit report from the BPK Jambi Provincial Office, highlighting fundamental weaknesses in institutional planning within the governance and management of the Public Service Mall (MPP) in Jambi City. Conclusion: These insights suggest that strategic initiatives are essential to improve governance at the PTSP, enhancing citizen satisfaction and trust in local government.